Effect of perivascular low dose ethanol on rat femoral vessels: Preliminary study - Baş, Soysal; Özakkoyunlu Hasçiçek, Seyhan; Uçak, Ramazan; Günenç, Alican; Karasoy Yeşilada, Ayşin (Taylor and Francis Ltd., 2020)
Vasospasm is one of the important causes of morbidity in free flap and replantation surgery. In secondary Raynaud’s phenomenon, nearly half of the patients experience digital ulceration, pain and loss of function at least once in their lifetime. The aim of this study is to investigate the vasodilation effect of ethanol-mediated chemical denervation on peripheral vessels by topical administration. In this study, 27 Wistar albino male rats weighing 250-300 grams were used. The rats were randomly divided into three groups: saline (group S, n = 8), lidocaine (group L, n = 9) and 96% ethanol (group E, n = 9). According to group, 0.1 mL saline, 0.1 mL lidocaine and 0.1 mL ethanol were applied around the rat femoral neurovascular bundle. After the application, on the 0th day and 3th weeks, femoral artery and vein diameters were measured. After 3. weeks, histopathological samples from femoral artery, vein and nerve were evaluated. On the 0th day, the mean diameter of the femoral artery and vein was similar in group E and L and higher than group S. After three weeks, the vasodilatation effect of ethanol was increased in group E. In Group L and S, the vasodilatation effect was lost. Histopathological examination showed that ethanol significantly caused perivascular inflammation and nerve degeneration compared to other agents and did not cause endothelial damage. Vasodilatation obtained by ethanol is a rapid onset and long-lasting effect. It is also inexpensive and effective for peripheral vasodilatation.
Keywords: Ethanol; Microsurgery; Raynaud’s Phenomenon; Vasodilatation; Vasospasm